Study of maternal mortality trends: 10 years retrospective and comparative analysis at a tertiary teaching hospital of Gwalior Chambal region - Bindal, Jyoti; Solanki, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal death is a preventable calamity. The aim of this study was to analyze the causes of maternal mortality in a tertiary teaching hospital. Methods: The present study was done at Kamla Raja Hospital, G R Medical College and JA Group of Hospitals, Gwalior. We reviewed the records of antenatal patients admitted from January, 2005 to December, 2015. The records were analyzed for parameters related to maternal mortality. The change in trends and causes of maternal mortality in patients between 2005-2010 was compared with the patients admitted from 2010 to 2014. Results: During 2005-2009 a total of 28370 antenatal patients were admitted and 27711 live births took place, whereas in 2010-2014 a total 30355 patients were admitted and 29305 live births took place. A total 188 (0.66%) and 251(0.83%) maternal death took place from 2005-2009 and 2010-2014 respectively. Maternal death was more common in unbooked, low socioeconomic status and illiterate patients. The common causes of maternal death were eclampsia, hemorrhage and anemia. Conclusions: Delay in seeking emergency obstetric care and not having regular antenatal checkups by pregnant females are the major contributors for maternal mortality. Dedicated obstetric intensive care units at referral centers for prompt and comprehensive care may help in reducing the maternal morbidity and mortality.